PENGARUH PROFITABILITY DAN LEVERAGE TERHADAP DIVIDEND POLICY DENGAN LIQUIDITY SEBAGAI PEMODERASI - Melita Mulyani; Rini Tri Hastuti (Jurnal Paradigma Akuntansi, 2023)
The purpose of this study was to obtain empirical evidence about the effect of profitability and leverage on dividend policy with liquidity as moderating in manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. Data on manufacturing companies that are in accordance with the requirements in this study using purposive sampling method. In this study using a total of 114 data. The technique used in data processing uses multiple regression analysis using the EViews V.12 program. In this study using secondary data, this secondary data is a financial report. The results obtained are that profitability has a significant effect on the dividend policy variable, while the leverage variable has no significant effect on the dividend policy variable and the liquidity variable cannot moderate the profitability variable and the leverage variable on the dividend policy variable.